2014
DOI: 10.1179/1607845414y.0000000195
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-intensity stem cell allografting for PNH patients in the eculizumab era: The Mexican experience

Abstract: Background Paroxysmal nocturnal haemoglobinuria (PNH) presents as two major entities: the classical form, predominantly haemolytic and a secondary type with marrow failure and resultant aplastic anaemia (AA-PNH). Currently, the treatment of choice of the haemolytic variant is eculizumab; however, the most frequent form of PNH in México is AA-PNH. Patients and methods Six consecutive AA-PNH patients with HLA-identical siblings were allografted in two institutions in México, employing a reduced-intensity conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The median age at the time of transplantation was 32 and the oldest patient was 51 years of age. In the literature, the median ages of patients were generally in the range of 24.5-37 years, but a patient as old as 60 years was transplanted [ 11 , 12 , 15 , 16 , 17 , 18 ]. The median time to transplantation was 36 months in our cohort, and patients received different therapies, including eculizumab (21 patients with a median of 24 months; minumum-maximum: 1-44 months).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median age at the time of transplantation was 32 and the oldest patient was 51 years of age. In the literature, the median ages of patients were generally in the range of 24.5-37 years, but a patient as old as 60 years was transplanted [ 11 , 12 , 15 , 16 , 17 , 18 ]. The median time to transplantation was 36 months in our cohort, and patients received different therapies, including eculizumab (21 patients with a median of 24 months; minumum-maximum: 1-44 months).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the rarity of this disease and other treatment options, although prospective randomized studies are lacking in the literature, the safety and efficiency of RIC regimens were demonstrated in small series [ 17 , 22 ]. By integrating RIC regimens with allo-HCT for PNH patients, the mortality and morbidity rates have been reduced, obviating the need for more potentially toxic myeloablative therapies [ 16 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to microgravity during space flight is known to involve a variety of health risks to the human body, increasing vulnerability to secondary conditions like radiation effects and physiological changes such as muscle atrophy, lysis, neocytolysis, metabolic variations, and hydrostatic pressure changes (Schimmerling, 1995;Schcolnik-Cabrera et al, 2014;Buonanno et al, 2015). Microgravity conditions and radiation can stimulate a variety of stressors in astronauts during spaceflight with negative consequences for their health (Garrett-Bakelman et al, 2019;Afshinnekoo et al, 2020).…”
Section: Red Blood Cells Behavior Under Microgravity Conditionsmentioning
confidence: 99%
“…14 Because of the rarity of PNH, the incidence and prevalence rates have been poorly reported and have likely been underestimated. 12,15 However, for stakeholders to best night (nocturnal) hemoglobin occurring in the urine (hemoglobinuria, passing of breakdown product of RBCs into urine). 8 However, hemoglobin in the urine may not always be visible to the eye, and not every patient with PNH presents with frank hemoglobinuria.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%